The use of Code of Conduct as instrument of management control: a case study in internationalized companies - Silva, Vaner Guimarães da (2009)
Nowadays, the ethical behavior on the part of the companies is waited and demanded by the society, being an important requirement so that the enterprises can increase its possibilities of success in the short and in the long stated period. Considering that the objective of the company is to add value to its shareholders, and observing the relevance of the ethical subject in the organizations, companies in all the world have been implementing codes of conduct that search to establish clearly the values of the company, guiding the actions of the components organization and this way, acting as an instrument of management control and corporative governance. In this context, the study had as objective to analyze the mains approaches used in the code of ethical conduct of a sample of twelve internationalized companies, and verify how this document can be used as an instrument of management control. After the analysis of the codes was observed that the topics: relationships with suppliers, relationships with customers, discrimination of employees, relationship with investors, environment, act of receiving of gifts and toasts, conflicts of interests and privileged information had the most frequency of mention. After the establishment of the necessary points for the correct functioning of an ethical control system, verified in the literature’s revision, and the survey of the practices of the internationalized companies analyzed, was possible to observe that only two of the twelve companies are in conformity or present greater proximity to the described premises by the main authors and the rules highlighted in this study.